Pichia pastoris secreted peptides crossing the blood-brain barrier and DSIP fusion peptide efficacy in PCPA-induced insomnia mouse models - Mu, Xiaoxiao; Qu, Lijun; Yin, Liquan; Wang, Libo; Liu, Xiaoyang; Liu, Dingxi (Frontiers in Pharmacology, 2024)
Background: Pichia pastoris-secreted delta sleep inducing peptide and crossing the blood-brain barrier peptides (DSIP-CBBBP) fusion peptides holds significant promise for its potential sleep-enhancing and neurotransmitter balancing effects. This study investigates these properties using a p-chlorophenylalanine (PCPA) -induced insomnia model in mice, an approach akin to traditional methods evaluating sleep-promoting activities in fusion peptides. Aim of the study: The research aims to elucidate the sleep-promoting mechanism of DSIP-CBBBP, exploring its impact on neurotransmitter levels and sleep regulation, and to analyze its composition and structure. Materials and methods: Using a PCPA-induced insomnia mouse model, the study evaluates the sleep-promoting effects of DSIP-CBBBP. The peptide's influence on neurotransmitters such as 5-HT, glutamate, dopamine, and melatonin is assessed. The functions of DSIP-CBBBP are characterized using biochemical and animal insomnia-induced behavior tests and compared without CBBBP. Results: DSIP-CBBBP demonstrates a capacity to modulate neurotransmitter levels, indicated by changes in 5-HT, glutamate, DA, and melatonin. DSIP-CBBBP shows a better restorative effect than DSIP on neurotransmitter imbalance and the potential to enhance sleep. Conclusions: The study underscores DSIP-CBBBP potential in correcting neurotransmitter dysregulation and promoting sleep, hinting at its utility in sleep-related therapies.